Participatory Fan Culture and the Phenomenon of Celebrity Worship in Indonesia: An Analysis of the Artist Raffi Ahmad through the Perspective of Henry Jenkins' Theory - Fatmawaty Rumra; Deddy Mulyana (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2026)
This study seeks to examine the phenomenon of participatory fan culture and practices of celebrity worship surrounding Indonesian artist Raffi Ahmad by applying Henry Jenkins’ theoretical framework on media convergence and participatory culture. This research is designed as an intrinsic case study, focusing specifically on the Indonesian digital ecosystem to provide an in-depth understanding of a particular cultural phenomenon and to avoid overgeneralization beyond this context. Using a qualitative research design, the study employs digital content analysis combined with virtual ethnography to explore how participatory practices and celebrity worship are constructed and sustained among Raffi Ahmad’s fans across multiple digital media platforms in Indonesia. The results show that fans are not positioned merely as passive audiences, but rather as active participants and content producers, or prosumers. They actively create and circulate fan-made content such as video edits, memes, reaction videos, and promotional materials related to RANS Entertainment. Furthermore, fans develop strong parasocial relationships facilitated by real-time interactions through live streaming features, which reinforce the perception of two-way intimacy between the celebrity and his audience. The research also identifies processes of absorption that, in some cases, evolve into addictive patterns of media use. These are reflected in behaviors such as continuous monitoring of celebrity-related content, fear of missing out (FOMO), and habitual doomscrolling. From a psychological perspective, Raffi Ahmad’s content provides emotional comfort for some fans, while for others it functions as a form of digital escapism from everyday pressures.